The use of crossword puzzles to enhance the learning of english nouns and verbs among year six pupils of Sekolah Kebangsaan St Patrick Semadang / Febian Siges - Siges, Febian (2004)
The purpose ofthis study was to find out whether the uses of crossword puzzles enhance the learning of English nouns and verbs among ESL learners in the primary school. Using crossword puzzles , it was found that after three weeks( 05.09.2004 until 22.09.2004 ), the pupils who were taught the English language achieved significantly progress in their language and they easily manage to overcome their passiveness. With crossword puzzles the students easily interact with their peers. It makes English language teaching much easier than before. It was concluded that the use of crossword puzzles for the teaching of English language in ESL classroom was very effective in improving learners’ interaction.